Facile reconstruction of microbial fuel cell (MFC) anode with enhanced exoelectrogens selection for intensified electricity generation - Kang, Y.L.; Pichiah, S.; Ibrahim, S. (Elsevier, 2017)
The present work emphasized on the enhancement of microbial fuel cell (MFC) anode through the utilization of conductive polymer. The conductive polymer, poly(3,4-ethylenedioxythiophene) (PEDOT) was coated with varied concentrations onto graphite felt base anodes. The findings demonstrated that the optimum loading of 2.5 mg/cm2 recorded maximum current density of 3.5 A/m2 and coulombic efficiency of 51%. Higher loading of PEDOT enhanced the electrochemical characteristics of the anodes but exhibited unfavorable functionality. The charge transfer resistance of the modified anodes, Ra decreased significantly compared to the control anode after biofilm formation. The successful application of palm oil mill effluent (POME) wastewater as substrate indicates that the optimum anode was effective in degrading high organic wastewater. Exoelectrogens were found to be distributed mainly on the anodic biofilm. The microbial diversity of the anodes varied greatly from the inoculum and Geobacter was identified as the prevailing exoelectrogen responsible for the power generation.